N-(5-Ethylsulfanyl-1,3,4-thiadiazol-2-yl)-2-(4,5,6,7-tetrahydrothieno[3,2-c]pyridin-5-yl)acetamide - Shuang Zhi; Shuai Mu; Ying Liu; Deng-Ke Liu (Acta Crystallographica Section E, 2011)
In the title compound, C13H16N4OS3, a thienopyridinederivative, the tetrahydropyridine ring exhibits a half-chair conformation, and the folded conformation of the molecule is defined by the N—C—C—N torsion angle of −78.85 (16)°. The crystal packing features intermolecular C—H...N, N—H...N and C—H...O hydrogen bonds.